Why Are Bifidobacteria Important for Infants? - Gerrit A. Stuivenberg; Jeremy P. Burton; Peter A. Bron; Gregor Reid (Microorganisms, 2022)
The presence of Bifidobacterium species in the maternal vaginal and fecal microbiota is arguably an evolutionary trait that allows these organisms to be primary colonizers of the newborn intestinal tract. Their ability to utilize human milk oligosaccharides fosters their establishment as core health-promoting organisms throughout life. A reduction in their abundance in infants has been shown to increase the prevalence of obesity, diabetes, metabolic disorder, and all-cause mortality later in life. Probiotic strains have been developed as supplements for premature babies and to counter some of these ailments as well as to confer a range of health benefits. The ability to modulate the immune response and produce short-chain fatty acids, particularly acetate and butyrate, that strengthen the gut barrier and regulate the gut microbiome, makes Bifidobacterium a core component of a healthy infant through adulthood.